The Effect of Washing Dilute Acid Pretreated Poplar Biomass on Ethanol Yields - Frederick, Noaa; Zhang, Ningning; Djioleu, Angele; Ge, Xumeng; Xu, Jianfeng; Carrier, Danielle Julie (IntechOpen, 2013)
None